Developing a theory of peer mentorship in a knowledge translation trainee context. Issue 12 (2nd December 2019) - DeForge, Ryan; Colquhoun, Heather; Richmond, Sarah A.; Emberly, Debbie; Newman, Kristine
ABSTRACT: Background: Knowledge translation (KT) is an emerging field of practice, one in need of supports for growth, including, notably, peer mentorship. Aim: To enhance our understanding of peer mentorship, this qualitative research examines the lived experiences of peer mentorship among graduate students and junior faculty whose studies focus on knowledge translation (KT). Data collection and analysis: Interview data were collected from 12 members of a KT 'trainee collaborative' and were analyzed using grounded theory techniques. Findings: The resultant theory of peer mentorship views the phenomenon as distinct from traditional mentorship, and outlines antecedents deemed necessary for creating and optimizing the formation of peer mentorship relationships. The theory also delineates between active and passive participation in such relationships, both within the formative stages, and once a set of peers has begun to 'be in' the relationship. Conclusion: The model offers KT trainees and faculty an opportunity to reflect on peer mentorship practices, and to consider the conditions that may optimize peer mentorship.